New vibratory device for wrist rehabilitation - Oliveira, Ana (2019)
Wrist injuries are very common in most of the population, specially bone fractures, but also other pathologies such as tendinitis and neurological diseases. When the wrist is injured, their flexion-extension and radial-ulnar deviation and pronation-supination movements of the forearm are compromised and interdict most daily activities. Therefore, it is important to recover the normal functionality of the wrist, namely, the range of motion. In this paper, a new vibratory device for wrist rehabilitation is proposed. This device aims to overcome the main problems of the existing technologies, such as their price and complexity. For this purpose, two models were developed. In this work numerical simulations were performed, as well as experimental tests on patients and on the device itself. The devices promoted an increase of range of motion of the wrist and forearm at appropriate frequencies. Thus, they constitute an important complement to the rehabilitation process of patients with wrist injuries.